Integrating Disability, Transforming Feminist Theory - Garland-Thomson, Rosemarie (NWSA Journal, 2002)
This essay aims to amplify feminist theory by articulating and fostering feminist disability theory. It names feminist disability studies as an academic field of inquiry, describes work that is already underway, calls for needed study and sets an agenda for future work in feminist disability studies. Feminist disability theory augments the terms and confronts the limits of the ways we understand human diversity, the materiality of the body, multiculturalism, and the social formations that interpret bodily differences. The essay asserts that integrating disability as a category of analysis and a system of representation deepens, expands, and challenges feminist theory. To elaborate on these premises, the essay discusses four fundamental and interpenetrating domains of feminist theory: representation, the body, identity, and activism, suggesting some critical inquiries that considering disability can generate within these theoretical arenas.
Keywords: EDI; activisme; approches et analyses; corps; cours; discipline; militance; premier cycle; queer; ressource en ligne; santé; sciences humaines; sciences sociales; sex1920; thématiques; études critiques du handicap; études féministes

Life during wartime: Emotions and the development of act up - Gould, Deborah (Mobilization: An International Journal, 2002)
Focusing on the street AIDS activist movement ACT UP, this article explores the question of social movement sustainability. Emotions figure centrally in two ways. First, I argue that the emotion work of movements, largely ignored by scholars, is vital to their ability to develop and thrive over time. I investigate the ways AIDS activists nourished and extended an “emotional common sense” that was amenable to their brand of street activism, exploring, for example, the ways in which ACT UP marshaled grief and tethered it to anger; reoriented the object of gay pride away from community stoicism and toward gay sexual difference and militant activism; transformed the subject and object of shame from gay shame about homosexuality to government shame about its negligent response to AIDS; and gave birth to a new “queer” identity that joined the new emotional common sense, militant politics, and sexradicalism into a compelling package that helped to sustain the movement. Second, I investigate the emotions generated in the heat of the action that also helped the street AIDS activist movement flourish into the early 1990s.
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; VIH; amériques; approches et analyses; identités LGBTQIA2+; militance; mouvements sociaux; périodes historiques; queer; ressource en ligne; régions géographiques; thématiques; émotions; états-unis

La "conscientisation" dans le militantisme des années 1970 - Mathieu, Lilian (Discours savants, discours militants: mélange des genres, 2002)
"OGM, nucléaire, principe de précaution, comité de sages, experts… autant de figures ou de domaines pour lesquels science et politique sont étroitement imbriquées. Le recours dans le débat public à la science et à l'expertise semble constituer une ressource politique susceptible de convaincre efficacement. Les auteurs montrent la diversité des usages militants des discours savants et saisissent les conditions de " passage " des discours d'un univers à l'autre."– Site de l'éditeur.
Keywords: 1900-1999; 1970-1979; approches et analyses; cours; cycles supérieurs; discipline; fem7000; histoire et politique; justice sociale; militance; pédagogie; périodes historiques; ressource en ligne; science politique; science politique et droit; thématiques

Standpoint theory, situated knowledge and the situated imagination - Stoetzler, Marcel; Yuval-Davis, Nira (Feminist Theory, 2002)
The aim of the article is to further assess and develop feminist standpoint theory by introducing the notion of the ‘situated imagination’ as constituting an important part of this theory as well as that of ‘situated knowledge’. The article argues that the faculty of the imagination constructs as well as transforms, challenges and supersedes both existing knowledge and social reality. However, like knowledge, it is crucial to theorize the imagination as situated, that is, as shaped and conditioned (although not determined) by social positioning.
Number: 3 https://journals-sagepub-com.proxy.bibliotheques.uqam.ca/doi/pdf/10.1177/146470002762492024
Keywords: approches et analyses; cours; discipline; fem1000; justice sociale; militance; mouvements sociaux; point de vue situé; premier cycle; ressource en ligne; sciences humaines; thématiques; théories féministes; épistémologie

The micro potential for social change: Emotion, consciousness, and social movement formation - Summers-Effler, Erika (Sociological Theory, 2002)
Can one explain both the resilience of the status quo and the possibility for resistance from a subordinate position? This paper aims to resolve these seemingly incompatible perspectives. By extending Randall Collins’s interaction ritual theory, and synthesizing it with Norbert Wiley’s model of the self, this paper suggests how the emotional dynam- ics between people and within the self can explain social inertia as well as the possibility for resistance and change. Diverging from literature on the sociology of emotions that has been concerned with individual emotional processes, this paper considers the collective level in order to explore how movement action is motivated. The emotional dynamics of subordinate positioning that limit women’s options in face-to-face inter- actions are examined, as are the social processes of developing feminist consciousness and a willingness to participate in resistance work. Pointing toward empirical appli- cations, I conclude by suggesting conditions where resistance is likely.
Keywords: changement social; discipline; féminisme; militance; mouvements féministes; ressource en ligne; résistance; sciences humaines; sociologie; thématiques; émotions

Loving internationalism: The emotion culture of transnational women's organizations, 1888-1945 - Taylor, Verta; Rupp, Leila (Mobilization: An International Quarterly, 2002)
Keywords: 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; allemagne; amériques; angleterre; discipline; droits des femmes*; europe; femmes* trans; france; militance; pays-bas; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques; émotions; états-unis